Evaluation of papaya genotypes using agronomic descriptors and estimation of genetic parameters - Dias, Nágela Lazare Pereira; de Oliveira, Eder Jorge; Dantas, Jorge Luiz Loyola (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate quantitative descriptors and to estimate genetic parameters in genotypes of papaya (Carica papaya). An experiment was settled using augmented blocks, for the evaluation of 27 genotypes, among cultivars, improved lines and local varieties with 30 descriptors related to the plant, leaves, flowers, fruit and seeds. After several cycles of breeding, the genotypes still showed broad variability for the evaluated descriptors. Most of the phenotypic variation occurred due to genetic variance. The heritability ranged from 60.48 to 99.05%, and in 80% cases it was higher than 80.46%. The ratio between genetic and environmental coefficients of variation, was greater than the unity for 63% traits. There are enough agronomic differences which allow for the use of the genotypes “per se” or as parents in breeding programs because they aggregate genetic variation, fruit quality and agronomic type.
Keywords: Carica papaya; variety development; genetic breeding; parental selection; genetic variation